Palladium-Catalyzed Asymmetric [3+2] Cycloaddition Reaction of Vinyl Cyclopropane with Electron-Deficient Dienes - Li, Yun-Fan; Yang, Cun; Xi, Yu-Ting; Tan, Qitao; Ding, Chang-Hua; Xu, Bin (Synlett, 2024)
Palladium-catalyzed asymmetric [3+2] cycloaddition reaction of vinyl cyclopropane and electron-deficient dienes was realized. The cycloaddition reaction proceeded regioselectively on the distant C=C double bond of electron-deficient dienes, and was mainly controlled by the steric hindrance of the 5-substituent of electron-deficient dienes. Chiral multi-substituted cyclopentanes bearing three functional groups (monosubstituted alkene, conjugated ester, and cyano) and three continuous stereocenters were obtained in moderate to high yields, diastereoselectivities, and enantioselectivities.
Keywords: palladium; [3+2] cycloaddition; vinyl cyclopropane; asymmetric catalysis; electron-deficient diene